NUCLEIC ACID AMPLIFICATION TEST FOR DETECTION OF WEST NILE VIRUS INFECTION IN PAKISTANI BLOOD DONORS - Niazi, Saifullah Khan; Alam, Maqbool; Yazdani, Muhammad Sajid; Ghani, Eijaz; Rathore, Muhammad Ali (Journal of Ayub Medical College Abbottabad, 2017)
Background: The study was planned to determine the presence of West Nile Virus (WNV) infection in Pakistani blood donors, using Nucleic Acid Amplification Test (NAT). Methods: The blood donors for study were selected on the basis of the standard questionnaire and routine screening results. Six donors were pooled using an automated pipettor and NAT for WNV was performed on Roche Cobas s 201 NAT system. The reactive pools were resolved in Individual Donation-NAT (ID-NAT) format and a sample from FFP bags of reactive donations was retrieved. NAT was again performed on retrieved plasma bag (RPB) sample to confirm the reactive donations. The donors were also recalled and interviewed about history of illness related to recent WNV infection. Results: After serological screening of 1929 donors during the study period, 1860 donors were selected for NAT test for WNV detection. The mean age of the donors was 28±8.77 (range: 18-57 years). 1847 (99.3%) donors were male and 13 (0.7%) were female. NAT for WNV identified six initially reactive pools (0.32%). On follow-up testing with RPB samples, 4 donors (0.21%) were found confirmed reactive for WNV RNA (NAT yield of 1 in 465 blood donors). Conclusion: WNV is a threat to safety of blood products in Pakistan. A screening strategy can be implemented after a large-scale study and financial considerations. One of the reduced cost screening strategies is seasonal screening of blood donors for WNV, with pooling of samples. Keywords: Nucleic Acid Amplification Test (NAT); West Nile Virus (WNV); Blood donors